2018
DOI: 10.1002/mar.21101
|View full text |Cite
|
Sign up to set email alerts
|

Counter‐stereotypical products: Barriers to their adoption and strategies to overcome them

Abstract: Counter‐stereotypical products (CSPs) are targeted at groups that are opposite to the stereotypical users of these products (e.g., face‐cream for men, construction tools for women). Such products entail adoption barriers, as they are associated with a dissociative out‐group (e.g., men avoid products used by women). A theoretical framework is developed to investigate such barriers by outlining consumers’ cognitive and affective responses to CSPs; namely: stereotyping (CSP is considered appropriate only for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Men seem to be particularly resistant to purchase products that signal femininity to maintain their gender identity (Antonetti & Maklan, 2016; Avery, 2012; Brough et al, 2016; Gal & Wilkie, 2010; Gill & Lei, 2018; Morris & Cundiff, 1971; Pinna, 2019; White & Dahl, 2006). For example, Shang and Peloza (2016) showed that consumption of ethical alternatives communicates higher femininity to external observers, which could be threatening for male consumers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Men seem to be particularly resistant to purchase products that signal femininity to maintain their gender identity (Antonetti & Maklan, 2016; Avery, 2012; Brough et al, 2016; Gal & Wilkie, 2010; Gill & Lei, 2018; Morris & Cundiff, 1971; Pinna, 2019; White & Dahl, 2006). For example, Shang and Peloza (2016) showed that consumption of ethical alternatives communicates higher femininity to external observers, which could be threatening for male consumers.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…2.2 | The negative impact of the feminine signal sent by green consumption on menʼs gender identity and mating desirability Some argue that this green-feminine stereotype could deter men from buying green products to protect their gender identity. Indeed, consumers sometimes choose products by copying a reference group, but they can also reject products by avoiding a dissociative group to maintain their identity (e.g., Bearden & Etzel, 1982;Gill & Lei, 2018;White & Dahl, 2006).…”
mentioning
confidence: 99%
“…Certain situations can challenge one's sense of meaning in life, resulting in an experience of a psychological threat (Baumeister & Vohs, 2002). Research in psychology and marketing shows that psychological threats such as stereotype threats (Gill & Lei, 2018;Steele & Aronson, 1995), threats to self-image (Gill & Lei, 2018;Thomas, Saenger, & Bock, 2017), threats to ego (Larson & Denton, 2014), and reminders of death (Heine et al, 2006) threaten one's sense of meaning in life.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, consumers can alter their product preferences and choice behaviors to circumvent social identity threat, avoiding products associated with the threatening aspect of identity (White & Argo, 2009). In support of these findings and broadening the research on social identity threat and consumer behavior, Gill and Lei (2018) develop a theoretical framework covering consumers’ negative responses to products threatening their social identity.…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 97%
“…These findings align with psychology research suggesting that individuals are motivated to avoid associating with marginal groups to maintain positive self‐worth (Branscombe & Wann, 1994; Doosje et al, 1995). Prior consumer behavior literature has closely examined the effects of social identity threat on consumer choices (Berger & Heath, 2008; Brough et al, 2016; Gill & Lei, 2018; White & Argo, 2009) and attitudes toward brands (Escalas & Bettman, 2005). For example, people avoid products associated with an out‐group to avoid signaling undesired identities (Berger & Heath, 2008) and tend to diverge from dissociative out‐groups to avoid social identity threat.…”
Section: Conceptual Development and Hypothesesmentioning
confidence: 99%